Pergeseran Makna Zakāt dalam Syair Arab Pra Islam dan Al-Quran - Sholihah, Inayatus; Bakar, Abu (Institut Agama Islam Negeri Kediri, 2023)
This study examines the shift in the meaning of the word zakāt in Arabic from the pre-Islamic period to the period when the Qur'an was revealed. This study refers to the book al-Taṭawwur al-Dalālī baina Lughah al-Shi’ri al-Jāhilī wa Lughah al-Qur'ān al-Karīm by ‘Ūdah Khalīl Abū ‘Ūdah which discusses terms in the Qur'an and their relationship with Jahiliyyah Arabic poetry. This research uses a descriptive-analytical method and a qualitative approach based on library research. The results of this study show that there are two main meanings of the word zakat, namely ‘increase or merit’ as the basic meaning during the Jahiliyyah (ma’nā lughawī) and ‘worship obligation to spend wealth’ as the new meaning introduced by the Qur’an (ma’nā iṣṭilāḥī). This shift in meaning not only affected the language but also affected the mindset, behavior, and social system of the Arab community, which was previously more individualistic to collective solidarity-based. Thus, the meaning of zakāt in the Qur'an reflects a significant moral and social transformation, making zakāt the main instrument in building the welfare of the people.